2009
DOI: 10.1016/j.ajic.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral action of common household disinfectants and antiseptics against murine hepatitis virus, a potential surrogate for SARS coronavirus

Abstract: Common household disinfectants and antiseptics were effective at inactivating MHV, a possible surrogate for SARS-CoV, from surfaces when used as directed. In an outbreak caused by novel agents, it is important to know the effectiveness of disinfectants and antiseptics to prevent or reduce the possibility of human-to-human transmission via surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 10 publications
5
102
0
1
Order By: Relevance
“…Antiseptic antiviral activity of common household disinfectants or antiseptics, containing either 0.05% of triclosan, 0.12% of chloroxylenol, 0.21% of sodium hypochlorite, 0.23% of pine oil, or 0.10% of a quaternary compound with 79.0% of ethanol, were investigated. All of them provided at least a 3 log 10 reduction in viral titers within a 30 sec contact time, which is consistent with the previous results [134]. …”
Section: Antisepsis-disinfection: An Efficient Weapon With Room Fsupporting
confidence: 92%
“…Antiseptic antiviral activity of common household disinfectants or antiseptics, containing either 0.05% of triclosan, 0.12% of chloroxylenol, 0.21% of sodium hypochlorite, 0.23% of pine oil, or 0.10% of a quaternary compound with 79.0% of ethanol, were investigated. All of them provided at least a 3 log 10 reduction in viral titers within a 30 sec contact time, which is consistent with the previous results [134]. …”
Section: Antisepsis-disinfection: An Efficient Weapon With Room Fsupporting
confidence: 92%
“…With the consideration of virus species, the disinfectant efficacy of the disinfectant against PEDV in this study showed higher than that tested by Dellanno et al (2009) and Tuladhar et al (2012), but lower than that tested by Tsao et al (1989).…”
Section: Resultsmentioning
confidence: 59%
“…In the results of the study by Dellanno et al (2009), the treatment with a QAC at the concentration of 1 mg/ml showed a 3-log reduction or better against murine hepatitis virus which belongs to a member of the family Coronaviridae such as PEDV. And the efficacy of quaternary ammonium chloride (QAC)-treated surfaces was examined to remove an enveloped virus, herpes simplex virus, and in the results, the titer of the virus was reduced by a factor of nearly 5 logarithm units in a 0.5% (v/v) bovine serum albumin solution (Tsao et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Quaternary ammoniums are supposed to be membrane-active products, which can explain the effect towards HSV-1 and other enveloped viruses in our current studies and those of other groups, obtained with a quaternary ammonium-based disinfectant [27,28,29]. Non-enveloped viruses are known to be resistant to quaternary ammonium [17,30], however a virucidal effect towards African horse sickness virus in suspension (member of the Reoviridae family) has been reported [28].…”
Section: Discussionmentioning
confidence: 63%